Coexistence of macroprolactinaemia and hyperprolactinaemia in women with oligo-/amenorrhoea is associated with high risk of pituitary adenomas. (May 2014) - Lewandowski, Krzysztof C.; Gasior-Perczak, Danuta; Kowalska, Aldona; Lewinski, Andrzej
Abstract Macroprolactin may cause elevation of prolactin (PRL) concentrations measured by standard assays. In our study, we assessed the prevalence of pituitary lesions in women with macroprolactinaemia and either oligomenorrhoea or secondary amenorrhoea. Pituitary MRI scans were performed in 61 women aged 31.0 ± 6.7 years (mean ± SD), with raised PRL concentrations due to macroprolactinaemia, detected by 25% polyethylene glycol (PEG) precipitation method (PRL recovery <40%). After PEG precipitation of macroprolactin, free PRL concentrations were still raised in 36 (59%) women. Microadenomas were detected in 10 patients out of 61 (16.4%), with raised free PRL in 9 of these cases, while macroadenomas were detected in 4 out of 61 (6.6%) women, all of whom also had raised free PRL. In case of coexistence of macroprolactinaemia and raised free PRL after PEG precipitation of macroprolactin, the chance of finding of either a micro- or a macroadenoma was 36% (13 cases out of 36). We conclude that hyperprolactinaemia and macroprolactinaemia may coexist in the same patient. Furthermore, if free PRL is raised after PEG precipitation of macroprolactin, then the chance of finding either a pituitary micro- or macroadenoma in women with oligo-/amenorrhoea is over 30%. Therefore pituitary magnetic resonance imaging is mandatory in all such cases.